Research on simulation of the bending fatigue test of automotive wheel made of long glass fiber reinforced thermoplastic considering anisotropic property. (February 2018) - Chai, Weihao; Liu, Xiandong; Shan, Yingchun; Wan, Xiaofei; Jiang, Er
Highlights: An automotive vehicle made of long glass fiber reinforced thermoplastic which has anisotropic property is studied. A combined simulation method for the wheel bending fatigue test considering the anisotropic property of the composite material is investigated. An anisotropic material model of the long glass fiber reinforced thermoplastic is established based on the tensile test of specimens. The accuracy of the simulation method and the anisotropic material model is validated by physical wheel bending fatigue test. Abstract: Using the long glass fiber reinforced thermoplastic composite (LGFT) in wheel manufacture is an important way for the lightweight design of automotive wheel. The bending fatigue test of automotive wheel is one of the key tests to ensure a safe wheel. Aiming at minimizing the development cost, this paper investigates a simulation method of the bending fatigue test considering the anisotropic property of the LGFT. First and foremost, the anisotropic material model of the LGFT is established based on the tensile test of LGFT specimens. With the fiber orientation and distribution of the wheel from the injection molding simulation, the anisotropic material property of the LGFT wheel is obtained. Then the simulation model of the bending fatigue test platform is established, with which the strength simulation of the LGFT wheel is conducted. To validate the accuracy of the simulation method and the anisotropic material model, the simulation results from the anisotropic/isotropic material models and the experimental result from the physical bending fatigue test are compared and analyzed. It can be seen that the result from the anisotropic material model satisfies the requirements well and is more accurate than that from the isotropic material model. The research shows that it is necessary to consider the anisotropic property in the strength simulation of the bending fatigue test of the LGFT wheel, and the simulation method considering anisotropic property provides an effective way for the strength simulation of other components made of the fiber reinforced thermoplastics.